Financial performance analysis using DuPont System at PT Unilever Indonesia Tbk - Fadelia, Regita; Musa, Muhammad Ichwan; Rahman, Abdul; Budiyanti, Hety; Nurman (Malaqbi Publisher, 2025)
Financial performance analysis using DuPont System at PT Unilever Indonesia Tbk